Women and retirement : strategies adopted by women as they adjust to retirement - Yeo, G. Cindy, 1962- (1991)
Thesis (M.A.)--Memorial University of Newfoundland, 1991. Sociology Bibliography: leaves 96-101 The objective of this thesis is to explore the process of retirement, in particular, the cognitive and defensive strategies adopted by retired professional and semi-professional women to maintain a sense of self in an urban Newfoundland community as they adjust to retirement. Since long term employment outside the home constitutes a salient experience for women, it is essential to examine its impact on retired women's sense of self, how factors such as ageism and sexism interact to influence women's identities and how their resources affect the way they respond to threatening situations. -- Using the symbolic interactionist approach and grounded theory, I interviewed a snowball sample of 11 retired professional and semi-professional women and three homemakers. All interviews were typically lengthy, diverse and semi-structured. Follow up interviews were held in a more casual atmosphere. The combination of built-in comparisons and indepth interviews indicate a great deal about the process of retirement adjustment and factors that influence it. -- Drawing from my data, retired women have differing sense of self and resources depending on whether or not they worked for pay, the nature of their work and home relationships. Although work has an impact on women's sense of self, this impact can be mediated by such factors as familial relationships. In addition, familial relationships like work experiences, can range from supportive to abusive. Consequently, retired women's areas of vulnerabilities and the strategies they devise to protect a positive sense of self vary from woman to woman. -- Like retired men, retired professional and semi-professional women have to deal with their own retirement. In addition, they have to deal with sexism, ageism, poverty and divorce. All these above mentioned factors affect women's sense of self and hence, their vulnerability to the retirement transition. With the increasing number of women in the labour force, female retirement has become a socially significant phenomenon. By exploring the difficulties retired women have to deal with in an effort to maintain their sense of self and the limited resources they have to protect themselves in threatening situations, we can have a better understanding of the kinds of threats they have to deal with and their needs. With this understanding, effective social policies can be implemented and retirement programs adjusted to serve the needs of both male and female retirees. Some of these policy issues are addressed in the concluding chapter.